О существовании кусочно-непрерывных сепаратрисных кривых одного класса импульсных систем - Свистун, О.П. (Український математичний журнал, 1994)
Sufficient conditions of existence of piecewise continuous separatrix curves are obtained for a certain class of systems of differential equations with pulse influence for small ε≥0.